Predicting death anxiety based on attachment to God with a self-fulfilling prophecy - Nouri, Razieh; Karimi, Mojtaba (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to predict death anxiety based on attachment to God with the moderating role of self-compassion. Methods: The research method is descriptive correlation; The statistical population of the present study was all cancer patients in Isfahan province in 2020. In this research, virtual random sampling method was called for volunteers to participate in this research. The instruments used in this study were the Templer Death Anxiety Questionnaire, the Short Form Self-Compassion Questionnaire and the Beck and McDonald Attachment to God Questionnaire (2004). Data analysis was analyzed by path analysis method in SPSS software. Results: Statistical analysis showed that avoidance and anxiety attachment to God and self-compassion were both able to significantly predict death anxiety (p <0.01). Conclusion: It can be said that different types of attachment to God have important effects on death anxiety in cancer patients and also self-compassion significantly mediates the relationship between attachment styles to God and death anxiety.